Education for Peace in Diversified Groups: Opportunities and Threats - JACHIMCZAK, BEATA (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2019)
Beata Jachimczak, Education for Peace in Diversified Groups: Opportunities and Threats. Interdisciplinary Contexts of Special Pedagogy, no. 27, Poznań 2019. Pp. 13–27. Adam Mickiewicz University Press. ISSN 2300-391X. e-ISSN 2658-283X. DOI: https://doi.org/10.14746/ikps.2019.27.01 The text addresses the problem of social changes related to the interpenetration of people with different cultures, religions, skills or nationalities in a common space, which also means that education is becoming more and more diverse in educational institutions. The transition from homogeneous groups to diverse groups in education has been and continues to be difficult due to many social, organizational and financial barriers. The analysis presented here relate to education for peace as a significant focus on a school (group) open to any individual difference as a resource for understanding oneself and the Other.